The Ultimate Division of Matter - de Souza, Mário Everaldo (Scientia Plena, 2011)
This work proposes that quarks are composite particles, composed of prequarks (called primons in this work) which are very light fermions. In this way we can explain the number of quarks and begin to understand why their masses cover a wide range of values. Moreover, we can understand what is behind the Kobaiashi-Maskawa matrix. Also, the proposal agrees with the experimental data of the recent RHIC data.